Air quality impacts of a CicLAvia event in Downtown Los Angeles, CA. (January 2016) - Shu, Shi; Batteate, Christina; Cole, Brian; Froines, John; Zhu, Yifang
Abstract: CicLAvia in Los Angeles, CA is the open streets program that closes streets to motorized vehicles and invites people to walk, run, play or ride their bicycles on these streets, allowing them to experience the city in a new way and get exercise at the same time. Since the events reduce the motorized traffic flow, which is a significant source of air pollution, on the streets, it is reasonable to hypothesize that the CicLAvia events can reduce the concentrations of traffic-emitted air pollutants during the road closure. This study is the first experiment to test this hypothesis. The on-road and community-wide ultrafine particle (UFP) and PM2.5 were measured on the Event-Sunday (October 5th, 2014) and the Pre- and Post- Sundays (September 28 th and October 12 th, 2014). Data analysis results showed the on-road UFP and PM2.5 reduction was 21% and 49%, respectively, and the community-wide PM2.5 reduction was 12%. Highlights: A natural experiment on air quality impacts of one CicLAvia event was conducted. The CicLAvia event reduced traffic flow from 1, 100 vehicles h −1 to zero. On-road ultrafine particle and PM2.5 reduction was 21% and 49% respectively. Community-wide PM2.5 reduction was 12%. Abstract : This study showed the CicLAvia event on October 5th, 2014 had reduced the on-road and community-wide concentrations of ultrafine particles and PM2.5 .